The Leadership Role of The Madrasah Head In Developing Teacher Professionalism - Arifin, Samsul (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
This research aims to explain the leadership role of the madrasa head as a leader and manager in developing teacher professionalism at Madrasah Aliyah Negeri 1 Situbondo. This research uses a qualitative approach, a case study type, a technique for determining research subjects with purpose, and data collection techniques using (1) semi-participant observation, (2) semi-structured interviews, and (3) documentation. Meanwhile, data analysis uses Miles Huberman and Saldana's interactive model with the following steps: (1) data collection, (2) data condensation, (3) data presentation, and (4) concluding. Triangulation and member checks are used to measure data validity. Three types of triangulations are used, namely source and method triangulation. Research results are 1). The leadership role of the madrasah head as a leader in developing teacher professionalism at Madrasah Aliyah Negeri 1 Situbondo: The madrasah head makes planning, implementation, and evaluation as well as work programs, such as drafting and creating semester programs together with teachers. Implementing teacher delegation in workshop or training activities periodically requires every teacher to update learning tools (content, methods, media, teaching materials in the lesson plan), provide advice, motivation, and suggestions, and solve problems in dealing with issues in madrasas related to teaching and learning, and provide leeway and flexibility for teachers who wish to pursue higher education or a master's degree. 2). The leadership role of the madrasa head as a manager in developing teacher professionalism at Madrasah Aliyah Negeri 1 Situbondo: The madrasa head provides opportunities for students to develop their talents and interests to improve the quality of the madrasa, creating an atmosphere that builds teacher discipline, class supervision and teacher performance assessment and provide evaluation of the results of class supervision by providing input on errors/discrepancies found and providing solutions to teachers at Madrasah Aliyah Negeri 1 Situbondo.